Nanolithographic Top‐Down Patterning of Polyoxovanadate‐Based Nanostructures with Switchable Electrical Resistivity. Issue 11 (21st August 2020) - Rösner, Benedikt; Fallica, Roberto; Johnson, Manuel; Späth, Andreas; Fink, Rainer; Ekinci, Yasin; David, Christian; Anjass, Montaha H.; Streb, Carsten
Abstract: The top‐down lithographic fabrication of functional metal oxide nanostructures enables technologically important applications such as catalysis and electronics. Here, we report the use of molecular vanadium oxides, polyoxovanadates, as molecular precursors for electron beam lithography to obtain functional vanadium oxide nanostructures. The new resist class described gives access to nanostructures with minimum dimensions close to 10 nm. The lithographically prepared structures exhibit temperature‐dependent switching behaviour of their electrical resistivity. The work could lay the foundation for accessing functional vanadium oxide nanostructures in the sub‐10‐nm domain using industrially established nanolithographic methods. Abstract : The top‐down fabrication of ∼10 nm vanadium oxide nanostructures by electron beam lithography based on a molecular vanadium oxide resist material is reported. The new material enables the large‐scale deposition of electrically switchable nanostructures which can be directly incorporated in established e‐beam lithography. The findings could in future enable the top‐down fabrication of functional metal oxide nanostructures in the < 10 nm domain.